Parametric study of esterification of free fatty acids derived from Ceiba Pentandra seed oil using microwaveassisted technique via response surface methodology - Lieu, T. (Italian Association of Chemical Engineering - AIDIC, 2015)
Biodiesel is an alternative fuel to conventional petroleum diesel. Due to economic and social concerns, the use of edible vegetable oils and animal fats should be replaced by non-edible plant oils for biodiesel production. In this regard, the oil from tropical plant Ceiba Pentandra is an attractive potential feedstock. However, like other non-edible feedstocks, C. Pentandra seed oil contains high free fatty acids (FFA) which negatively affect the process of biodiesel production. In the present work, acid esterification process was applied as a pre-treatment to reduce FFA content. By using microwave-assisted technique, the optimum conditions for diminishing the FFA content in the seed oil to 0.388 were found to be 2.0 wt H2SO4 catalyst, 10:1 methanol to oil molar ratio at 60 Â°C within 12 minutes of reaction time. In addition, an investigation on the effect of different acid catalysts such as hydrochloric acid and phosphoric acid as well as different solvents such as ethanol, 1-propanol and 2-propanol to obtain the best result based on optimum conditions was carried out. Sulfuric acid and methanol were found to be the best option for pretreatment of Ceiba Pentandra feedstock. Copyright Â© 2015, AIDIC Servizi S.r.l.,.